2020
DOI: 10.1111/1744-7917.12868
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory mechanisms of microbial homeostasis in insect gut

Abstract: Insects live in incredibly complex environments. The intestinal epithelium of insects is in constant contact with microorganisms, some of which are beneficial and some harmful to the host. Insect gut health and function are maintained through multidimensional mechanisms that can proficiently remove foreign pathogenic microorganisms while effectively maintaining local symbiotic microbial homeostasis. The basic immune mechanisms of the insect gut, such as the dual oxidase-reactive oxygen species (Duox-ROS) syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 163 publications
(279 reference statements)
1
52
0
Order By: Relevance
“…Insects provide a stable living environment and essential nutrients for intestinal microorganisms, which are also involved in a variety of insect metabolic processes, providing some nutrients for insects and digesting complex carbohydrates [2]. It has been widely confirmed that symbiotic microorganisms participate in the metabolism of the host [3,4], degrade exogenous biological toxins [5][6][7], help the host absorb nutrients [8], regulate the host's adaptability [4,9], protect the host from pathogens [10,11], regulate mating and reproduction [12,13], promote growth and development [14], and affect the transmission efficiency of vector insects [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Insects provide a stable living environment and essential nutrients for intestinal microorganisms, which are also involved in a variety of insect metabolic processes, providing some nutrients for insects and digesting complex carbohydrates [2]. It has been widely confirmed that symbiotic microorganisms participate in the metabolism of the host [3,4], degrade exogenous biological toxins [5][6][7], help the host absorb nutrients [8], regulate the host's adaptability [4,9], protect the host from pathogens [10,11], regulate mating and reproduction [12,13], promote growth and development [14], and affect the transmission efficiency of vector insects [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The intestinal epithelium of insects is in constant contact with microorganisms, which can be beneficial or harmful to the host. Gut health and functions are maintained through several mechanisms that can efficiently remove foreign pathogenic microorganisms, preserving the resident microbiota (Bai et al, 2021). ROS has a role in insect innate immune response as a potent pathogen-killing agent.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, ROS are pathogen-killing molecules, and their uncontrolled production destroys the microbiota homeostasis, leading to disease development in the host (Bai et al, 2021). The reduced expression of immuneregulated catalase causes high mortality rates in flies after oral infection, highlighting the importance of these reactive species for the host survival during continuous gastrointestinal exposure (Ha et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, advancements in next-generation sequencing allowed for a new understanding of the microbial complexity tightly associated with living beings and environments. Recent research demonstrated that microbiomes play a key role in the health of the organisms whom they are associated with, influencing, among others, their physiology, biochemistry, and reproductive success (Dinan and Cryan, 2017;Bai et al, 2020;Compant et al, 2020). In fact, the disruption of microbial homeostasis leads to dysbiosis, a condition which plays a major role in disease in humans and other animals (Liu et al, 2020), and decline in plants (Bettenfeld et al, 2020).…”
Section: Introductionmentioning
confidence: 99%